2022
DOI: 10.1145/3555118
|View full text |Cite
|
Sign up to set email alerts
|

"That Robot Played with Us!" Children's Perceptions of a Robot after a Child-Robot Group Interaction

Abstract: The design of child-centred, intelligent and collaborative robots is a challenging endeavour, which requires to understand how the implemented robot behaviours and collaboration paradigms affect children's perception about the robot. This paper presents the results of a set of semi-structured interviews of N=81, 5 to 8 years old children who previously interacted in pairs with a robot in the context of a problem-solving task. We manipulated two different factors of the robot behaviour: cognitive reliability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Social robots need to be designed in a way that they are child-centred and collaborative because robot behaviours and collaboration paradigms affect children's perception about the robot. Escobar-Planas et al (2022) found that cognitive reliability of the robot shapes the helping relationship between the children and the robot, while the robot's expressivity impacts the perception of the robot's support ability and friendship.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…Social robots need to be designed in a way that they are child-centred and collaborative because robot behaviours and collaboration paradigms affect children's perception about the robot. Escobar-Planas et al (2022) found that cognitive reliability of the robot shapes the helping relationship between the children and the robot, while the robot's expressivity impacts the perception of the robot's support ability and friendship.…”
Section: Fundingmentioning
confidence: 99%
“…Moreover, as collaborative partners, these robots encourage teamwork, discussions, critical thinking, and creativity, contributing significantly to social development ). They also offer emotional support by engaging in conversations and providing encouragement, beneficial for students facing stress or loneliness (Escobar-Planas et al (2022)). Through equipped cameras and remote capabilities, robots enable virtual field trips, enriching understanding in geography, history, or scientific phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Fields including HCI/CSCW and HRI have explored ethnography as a method to study work practices, technology use contexts, and accordingly guide the design of robotic technologies. In HCI/CSCW, for example, ethnography has been used to understand people's perception of robots [36][37][38], examine users' encounters with existing robots [39][40][41], co-design conceptual scenarios for human-robot collaboration [42], or reveal robots' impact on collaboration in surgery and manufacturing contexts [43][44][45]. To a lesser degree, the field of HRI also engaged with ethnographic approaches to guide technology design [46][47][48][49][50][51][52].…”
Section: Ethnography To Inform Construction Roboticsmentioning
confidence: 99%